2020
DOI: 10.1515/jcim-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and inflammatory mediators are associated with cytotoxic, anti-inflammatory and apoptotic activity of honeybee venom

Abstract: ObjectiveThe present study aimed to evaluate cytotoxic, apoptotic, and anti-inflammatory properties of bee venom (BV) as well as changes in cytokine secretion levels and nitric oxide (NO) production using three different cancer cell lines [liver (Hep-G2), breast (MCF-7), and cervical (HPV-18 infected HeLa cells)] and two normal cells (splenocytes and macrophages (MQ).MethodsCytotoxic activity of BV against tumor cell lines and normal splenocytes/MQ was tested by MTT assay. By ELISA (ELISA); Tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In recent years, several in vivo and in vitro studies reported that chemical constituents found in bee venom can be used in the treatment of diseases like cancer, arthritis, skin diseases, and diseases associated with the vascular system. Its promising positive effects have been reported against several cancers such as hepatocellular carcinoma, ovarian, prostate, breast, lung and urinary bladder cancer, and melanoma (Wehbe et al, 2019;Salama et al, 2021;Shi et al, 2022). The main constituent of bee venom is melittin which comprises 40%-50% of the total dry weight.…”
Section: Bee Venommentioning
confidence: 99%
“…In recent years, several in vivo and in vitro studies reported that chemical constituents found in bee venom can be used in the treatment of diseases like cancer, arthritis, skin diseases, and diseases associated with the vascular system. Its promising positive effects have been reported against several cancers such as hepatocellular carcinoma, ovarian, prostate, breast, lung and urinary bladder cancer, and melanoma (Wehbe et al, 2019;Salama et al, 2021;Shi et al, 2022). The main constituent of bee venom is melittin which comprises 40%-50% of the total dry weight.…”
Section: Bee Venommentioning
confidence: 99%
“…Additionally , melittin selectively targeted tumor cells because these cells possess high membrane potential as compared to normal cells ( Gajski et al, 2016a , Gajski et al, 2016b ) and the concentration, which was used against tumor cells, does not affect the normal cells growth ( Gajski and Garaj-Vrhovac 2013 ). Bee venom holds anti-tumor efficacy against different cancer cells like Breast cancer cell, Liver and Cervix cancer cells in a time and dose dependent way and have no side effect on non-target cells ( Salama et al, 2021 ).…”
Section: Pharmacological Properties Of Honey Bee Venommentioning
confidence: 99%